Lower Free Triiodothyronine Levels Within the Reference Range Are Associated with Higher Cardiovascular Mortality: an Analysis of the NHANES - Neves, JS (2019)
Thyroid hormones play a central role in cardiovascular homeostasis. Lower free triiodothyronine (FT3) levels have been associated with worse prognosis in several conditions. However, contrary to thyrotropin (TSH) and free thyroxine (FT4), the role of FT3 in morbidity and mortality in the general population remains uncertain. Our objective was to evaluate the association between within the normal range FT3 levels and mortality in the general population.